2020
DOI: 10.2174/1568026620666200124105027
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-DAD Assisted Phytochemical Quantitation Reveals a Sex, Ploidy and Ecogeography Specificity in the Expression Levels of Selected Secondary Metabolites in Medicinal Tinospora cordifolia: Implications for Elites’ Identification Program

Abstract: Background: Medicinal phytochemistry involving UPLC-DAD in an exhaustive analysis involving quantification of eight commercially important phytochemicals viz. syringin, cordifolioside A, magnoflorine, tinocordiside, palmatine, 20β-hydroxyecdysone, L-tetrahydropalmatine and berberine has been done in 143 accessions from eight states and the union territories of Delhi and Jammu & Kashmir of India representing three different ploidy levels viz. diploid (2x), triploid (3x) and synthetic tetraploid (4x). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Factors like soil, temperature, water, humidity, and species association have contributed substantially to these variations in TC. This quantification data showed a set of new contributing factors like the maturity of the stem, harvesting time with the influence of season, and association with this creeper [26, 27, 39, 40]. Further, this method and qualitative fingerprinting can provide an important clue in chemotaxonomy studies to understand this significant relationship lacking in previous reports.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Factors like soil, temperature, water, humidity, and species association have contributed substantially to these variations in TC. This quantification data showed a set of new contributing factors like the maturity of the stem, harvesting time with the influence of season, and association with this creeper [26, 27, 39, 40]. Further, this method and qualitative fingerprinting can provide an important clue in chemotaxonomy studies to understand this significant relationship lacking in previous reports.…”
Section: Discussionmentioning
confidence: 98%
“…Previous analytical studies on TC were focused on quantifying the isoquinoline alkaloids using simple TLC and LC-based techniques [19,24,25]. However, it is essential to focus on the compounds responsible for its protective effects with specific analytical or biomarkers from TC [26,27]. The recent LC-based MS/MS and Quadrupole-TOF studies have identified chemical markers from TC for quality control (QC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC analysis has been used as a preferred method for isolation, chemical characterization, and quantification of phytochemicals in many medicinal plant species (Han et al 2008;Sultan et al 2008;Thapliyal et al 2012;Song et al 2015;Mehra et al 2017;Thakur et al 2020).The concentration of picrosides in dry rhizomes of different populations of P. kurroa, has been found to vary with altitude in different ecogeographical regions in Himalayas. In Himachal Pradesh, the highest concentration of P-I and P-II was observed between an altitude of 2733 m (Sainj) to 2750 m (Parsuthach), in Uttarakhand it was observed between 3580 m (Dayara) to 3680 m (Tungnath), while in Kashmir and Sikkim regions, it was observed at 3000 m altitude in Arampatri and Temza, respectively.…”
Section: Discussionmentioning
confidence: 99%